2015
DOI: 10.1039/c5tb00887e
|View full text |Cite
|
Sign up to set email alerts
|

Double hydrophilic polyphosphoester containing copolymers as efficient templating agents for calcium carbonate microparticles

Abstract: The use of calcium carbonate (CaCO 3 ) microparticles is becoming more and more attractive in many fields especially in biomedical applications in which the fine tuning of the size, morphology and crystalline form of the CaCO 3 particles is crucial. Although some structuring compounds, like hyaluronic acid, give satisfying results, the control of the particle structure still has to be improved. To this end, we evaluated the CaCO 3 structuring capacity of novel well-defined double hydrophilic block copolymers c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 90 publications
0
15
0
Order By: Relevance
“…Frank and coworkers used D2 to form anionic hydrophilic PPE-copolymers as efficient templating agent for calcium carbonate particles. 324,325 Wang and coworkers 326 reported a cyclic phosphate carrying an allyl pendant group (2-(prop-2-en-1-yloxy)-2-oxo-1,3,2-dioxaphospholane, D3), which was polymerized with a PEG-macroinitiator. The block copolymers self-assembled into nanoparticles and the allyl groups were post-modified by thiol-ene reaction with cysteamine and partially further reacted with dimethyl maleic anhydride to introduce pH-responsivity.…”
Section: Cyclic Phosphatesmentioning
confidence: 99%
“…Frank and coworkers used D2 to form anionic hydrophilic PPE-copolymers as efficient templating agent for calcium carbonate particles. 324,325 Wang and coworkers 326 reported a cyclic phosphate carrying an allyl pendant group (2-(prop-2-en-1-yloxy)-2-oxo-1,3,2-dioxaphospholane, D3), which was polymerized with a PEG-macroinitiator. The block copolymers self-assembled into nanoparticles and the allyl groups were post-modified by thiol-ene reaction with cysteamine and partially further reacted with dimethyl maleic anhydride to introduce pH-responsivity.…”
Section: Cyclic Phosphatesmentioning
confidence: 99%
“…However, in the strict sense, these polymers are not biodegradable. The second type of these prospective polymers can be prepared by the ring-opening polymerization (ROP) of cyclic ethylene phosphate monomers [20][21][22][23][24] followed by the transformation of poly(ethylene phosphate)s to poly(ethylene phosphoric acid)s (PEPA) or their salts [25][26][27][28][29][30][31] (Scheme 1b). The mild thermolysis of the polymers of tert-butyl ethylene phosphate ( t BuOEP) was found to be a simple and efficient method of PEPA preparation (Scheme 1c) [32,33].…”
Section: Introductionmentioning
confidence: 99%
“…Penczek and coworkers [26,27] synthesized the triblock copolymer poly(ethylene glycol)-poly(alkylene phosphate)-poly(ethylene glycol) and found that it modulated the crystallization of CaCO 3 particles, resulting in the formation of unique features consisting of semi-open empty spheres that were composed of small crystallites with a diameter of 40-90 nm. Christine et al also studied the templating capacity of PPDEs for the synthesis of CaCO 3 particles [28]. [29].…”
Section: Mineral Affinity Of Polyphosphodiesters (Ppdes)mentioning
confidence: 99%